Hungary : Selected Issues. (IMF Staff Country Reports; Country Report, 2003)
This Selected Issues paper examines the external sector issues in Hungary. It looks at some traditional indicators of external competitiveness, and provides basic background on key macroeconomic developments, including the current account and its financing. The paper examines various measures of the real effective exchange rate, the labor market considerations, and actual export performance. The paper concludes that although external competitiveness of the Hungarian economy has not been permanently impaired and the country is doing well from various vantage points, a significant dent has been put in competitiveness.